Preditores de mortalidade e recuperação funcional após traumatismo cranioencefálico grave: um estudo observacional prospectivo do tipo coorte - Goncalves, Jéssica Vaz (2023)
Severe Traumatic Brain Injury (TBI) is a significant global public health issue, considered the leading cause of mortality and disability in young adults. Some clinical, neurosurgical, and sociodemographic factors have already been described as predictors of higher risks of in-hospital mortality and lower levels of functional recovery after the traumatic event. Identifying these predictive factors is crucial for guiding treatment and prognosis strategies, as well as shaping public health policies for this population. The aim of this study was to identify predictors of mortality and functional recovery from hospital admission up to 12 months after severe TBI. This was a prospective observational cohort study conducted at a trauma referral hospital in the state of Espírito Santo, Brazil. All individuals diagnosed with severe TBI over the age of 18 admitted within a one-year period were included. The analyzed outcomes were in-hospital mortality and functional recovery assessed using the Extended Glasgow Outcome Scale (GOSE) at the time of hospital discharge, 3, 6, and 12 months after TBI. After applying the inclusion criteria, 383 patients were included, of which 211 (55%) died, and 172 (45%) survived hospitalization. Among these, 145 completed the one-year follow-up. The mean age was 49 years, 80% were male, and falls (46.5%) were the main cause of injury. In the final binomial logistic regression model, age over 65 years, days on mechanical ventilation, and low educational level were strong predictors of unfavorable functional recovery over the 12 months following the trauma. Pupillary changes, such as anisocoria and mydriasis, high respiratory rate, decreased body temperature, ISS scores >25, and the performance of decompressive craniectomy were associated with a higher risk of in-hospital mortality. This study was the first to investigate predictors of mortality and functional recovery one year after severe Traumatic Brain Injury in the Brazilian population. The higher mortality rate in TBI patients compared to both high-income countries (HICs) and low- and middleincome countries (LMICs) underscores the importance of considering regional disparities when developing and implementing TBI management strategies worldwide.